Enhancing Teacher Performance Through the Strengthening of Organizational Culture, Compensation, and Work Motivation - Radina Qisma Jabar Sasmita; Hari Muharam; Griet Helena Laihad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines the ongoing challenges in improving teacher work performance at private vocational high schools through the strengthening of organizational culture, compensation, and work motivation. The aim of this research is to empirically test the causal relationships among these variables. The method used is a quantitative explanatory survey involving 128 teachers selected through proportional random sampling. Data were collected using a Likert-scale questionnaire, with validity tested through the Pearson Product Moment and reliability through Cronbach’s Alpha. Data analysis included prerequisite tests (normality, homogeneity, linearity, and significance) and path analysis to identify direct and indirect effects. The results show that organizational culture, compensation, and work motivation each have a significant direct effect on teacher performance, with work motivation emerging as the most dominant factor. Additionally, organizational culture and compensation also exert indirect effects through work motivation. These findings emphasize the importance of integrated empowerment strategies to enhance teacher performance. The study concludes that strengthening organizational culture, ensuring fair compensation, and implementing continuous motivation programs are essential to optimizing teacher work performance.